Delayed thoracodorsal nerve denervation for animation deformity following latissimus dorsi flap breast reconstruction: An 11-year retrospective analysis - Chloe Jordan; Krzysztof Sosnowski; Rushabh Shah; Kai Yuen Wong; Sarah Benyon; Michael Irwin; Charles Malata (JPRAS Open, 2025)
Introduction: Symptomatic animation deformity (AD) following latissimus dorsi (LD) flap breast reconstruction, though uncommon, significantly impacts patient satisfaction. Primary denervation is typically avoided due to potential intraoperative risk of damage to the LD vascular pedicle and subsequent muscle atrophy, which may necessitate future fat grafting. This study evaluates the incidence of troublesome AD requiring surgical intervention and assesses the safety and efficacy of selective delayed denervation in symptomatic patients at a UK university hospital. Materials and methods: Patients who underwent LD flap breast reconstruction between January 2014 and December 2024 were retrospectively analysed. Those with troublesome AD who subsequently underwent delayed denervation were identified. Data on demographics, surgical details, and outcomes were collected to evaluate the effectiveness and safety of delayed thoracodorsal nerve denervation. Results: Among 90 LD flaps in 84 patients (78 unilateral, 6 bilateral, mean age = 53.6 years, BMI = 25.8), 8.3 % (n = 7) reported troublesome AD, with almost half (n = 3) also experiencing pain. Delayed denervation was performed in all seven, with symptom improvement in six: complete resolution in 57.1 % (n = 4), partial relief in 28.7 % (n = 2), whilst one patient required redo surgery. No complications (e.g., infection, muscle atrophy, implant loss, rippling or long thoracic nerve damage) were reported. Conclusion: Our findings demonstrate that selective delayed thoracodorsal nerve denervation effectively manages symptomatic AD while avoiding overtreatment in asymptomatic patients. This approach preserves muscle volume, unlike primary denervation, and achieves a high success rate with minimal morbidity. Future prospective studies are required to establish standardised assessment criteria and optimal timing for intervention.